The effects of thromboxane synthase inhibition on reperfusion injury and endothelin-1,2 levels in allograft kidney transplantation in rats - HAKLAR, GONCAGÜL (SPRINGER VERLAG, 1999)
Thromboxane A(2) is a proaggregative vasoconstrictor that is synthesized and released in reperfusion injury. We aimed to investigate the effects of thromboxane synthase inhibitor, UK 38485, on endothelin-1,2 (ET) response of the renal endothelium and lipid peroxidation and protein oxidation in the early period of kidney transplantation. Four groups (n = 8) of Sprague-Dawley rats were designed as Group I (sham nephrectomy), Group II (autotransplantation), Group III (allotransplantation) and Group IV (allotransplantation group in which the allografts were perfused with UK 38485. All subjects underwent right nephrectomy after transplantation. The grafts were flushed with 4 mi of ice-cold Ringer's lactate and in Group TV 10 mu g of UK 38485 was added into the solution for each kidney. In allotransplantation groups, the kidneys were harvested from allogeneic white Wistar albino rats. The kidney grafts were allowed 120 min of reperfusion after 40 min of cold ischemic period. ET-1,2 plasma concentrations in the renal vein blood and diene conjugates (DC), hydroxyalkanals (HAA), hydroxyalkenals (HAE) and malondialdehyde (MDA) levels as the products of lipid peroxidation, protein carbonyls and protein sulfhydryls as the indicators of protein oxidation were analyzed in kidney tissue. Plasma ET-1,2 concentrations increased significantly in Group II and Group III(P<0.01) when compared to Group I but decreased in Group IV in comparison with Group III (P<0.05). DC, HAA, HAE and MDA levels increased in Groups II and III (P<0.001). Significant protein oxidation occurred only in Group III (P<0.01). Perfusion of the allografts with UK 38485 prevented lipid peroxidation and protein oxidation in Group IV. Histopathological changes were mild in the last group. We concluded that, in kidney transplantation, local administration of UK 38485 has cytopreservative effects on the allografts and this effect can be related to ET-1,2 concentrations.
Keywords: thromboxane; reperfusion injury; endothelin; kidney transplantation; FREE-RADICALS; SYNTHETASE INHIBITOR; PROSTAGLANDIN SYNTHESIS; RENAL-TRANSPLANTATION; WARM ISCHEMIA; COLD ISCHEMIA; REJECTION; CELLS; PROSTACYCLIN; PEPTIDES